Clinical profile of venomous snake bites in north Indian Military Hospital - Singh, Jasjit (Medknow Publications, 2008)
Snakebite is an environmental hazard associated with significant morbidity and mortality. We report a case series of venomous snakebites in a military operational area of north India. Of 33 cases of snake bites presenting to the military hospital, 21 patients were envenomated. The median age of patients was 24 years; all were men. All of the envenomations were neurotoxic in nature. Abdominal pain (91%), headache (86%), dysphagia (86%), ptosis (77%), diplopia (72%), blurred vision (72%), dyspnea (67%), and vomiting (62%) were the predominant clinical presentation. Polyvalent AntiSnakeVenom (ASV) [mean 180 ml; range 90-320 ml] was given to all patients with systemic manifestations, and repeated as needed. Eleven (52%) patients received neostigmine with glycopyrrolate to counter cholinergic effects. Two patients were given ventilatory support. The average time of recovery from envenomation was 16 hours after administration of ASV. All patients recovered without sequelae. Soldiers during military exercise are vulnerable to snakebites. Neurotoxic snakebites predominate in our study and usually present with autonomic features along with headache, abdominal pain, ptosis, diplopia and dysphasia. Preventive measures to minimize snake bites and planned treatment regimens should be emphasized among medical and military personnel deployed in the field operations.